Absence of cystic fibrosis mutations in a large Asian population sample and occurrence of a homozygous S549N mutation in an inbred Pakistani family. Issue 2 (February 1993) - Curtis, A; Richardson, R J; Boohene, J; Jackson, A; Nelson, R; Bhattacharya, S S
Abstract : The occurrence of cystic fibrosis is very rare in the Asian population. Carriers of the mutations most commonly found in Caucasians were not detected in a large Asian population sample of almost 900 chromosomes. However, an affected Pakistani child born to consanguineous parents was further investigated and shown to be homozygous for the mutation S549N (G-->A). Molecular and clinical data are presented which may improve our understanding of the phenotypic effects of the S549N mutation in the CFTR gene.